The Fiscal Smile : The Effectiveness and Limits of Fiscal Stabilizers - Silgoner, Maria (IMF Working Papers; Working Paper ;, 2003)
We study the smoothing impact of fiscal stabilizers (proxied by government expenditures or revenues) on business cycle volatility for a panel of EU countries in the period 1970-99. The results show that the business cycle volatility smoothing effect of fiscal stabilizers may revert at high levels. We present evidence that for government expenditure ratios exceeding an estimated value of about 38 percent, a further expansion in the size of the government could actually lead to an increase in cyclical volatility. This may call for a reconsideration of the use of fiscal stabilizers for business cycle smoothing.